Pemahaman Pelaku Nikah Muda Terhadap Konsep Keluarga Sakinah (Analisis Persepsi Kaum Muda) - Armi, Mhd. Ilham; Azwar, Zainal; Triasa, Arif Rahmat; Ulfa, Mawaddatul (Sekolah Tinggi Agama Islam Negeri Majene, 2023)
Young marriages have been massively practiced by young people in Indonesia. The rise of young marriage is a phenomenon in contemporary marital issues in Indonesia. The interest of young people to get married is a discussion that involves many new instruments to build a sakinah family in the household. This research will discuss young marriages conducted by men and women in the age range of 19-24 years when they get married. The data collection method uses a research questionnaire of 36 respondents (18 men and 18 women) collected randomly (random sampling). To test the respondents’ understanding in this study, the questionnaires were analyzed using a Guttman scale approach to interpret the extent of respondents’ understanding of the concept of a sakinah family. This study argues that the impetus for young marriage is due to the respondents’ religion and social arena. It can be explained that the consideration to marry at a young age is determined by these 2 instruments and is in line with the regulations set by the state. The 36 respondents were also measured for their level of understanding of the concept of a sakinah family. As a result, most of the 36 respondents in young marriages have fulfilled the personal competence, managerial competence, and competence to overcome discrimination as described in the concept of a sakinah family.